Slavery and the Missouri Compromise - Herschbach, Elisabeth (Building our nation., 2020)
Explores the role slavery and the Missouri Compromise played in the westward expansion of the United States. Discusses the arguments on each side of the slavery issue, and the deep divide slavery caused in the country. Includes a quiz with answer key, a glossary, color illustrations, and further resources.